Kawasaki Disease Increases the Incidence of Myopia. (30th July 2017) - Kung, Yung-Jen; Wei, Chang-Ching; Chen, Liuh An; Chen, Jiin Yi; Chang, Ching-Yao; Lin, Chao-Jen; Lim, Yun-Ping; Tien, Peng-Tai; Chen, Hsuan-Ju; Huang, Yong-San; Lin, Hui-Ju; Wan, Lei
Abstract : The prevalence of myopia has rapidly increased in recent decades and has led to a considerable global public health concern. In this study, we elucidate the relationship between Kawasaki disease (KD) and the incidence of myopia. We used Taiwan's National Health Insurance Research Database to conduct a population-based cohort study. We identified patients diagnosed with KD and individuals without KD who were selected by frequency matched based on sex, age, and the index year. The Cox proportional hazards regression model was used to estimate the hazard ratio and 95% confidence intervals for the comparison of the 2 cohorts. The log-rank test was used to test the incidence of myopia in the 2 cohorts. A total of 532 patients were included in the KD cohort and 2128 in the non-KD cohort. The risk of myopia (hazard ratio, 1.31; 95% confidence interval, 1.08–1.58; P < 0.01 ) was higher among patients with KD than among those in the non-KD cohort. The Cox proportional hazards regression model showed that irrespective of age, gender, and urbanization, Kawasaki disease was an independent risk factor for myopia. Patients with Kawasaki disease exhibited a substantially higher risk for developing myopia.